2018
DOI: 10.1016/j.jpainsymman.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Associated With Physical Function Trajectories in Older Adults With Cancer During Chemotherapy

Abstract: While several symptoms were associated with decrements in PCS scores at enrollment in older adults with cancer receiving chemotherapy, morning fatigue was the only symptom associated with decreases in physical function over time. Regular assessments of symptoms and implementation of evidence-based interventions should be considered to maintain physical function in older adults during chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 71 publications
2
11
0
Order By: Relevance
“…Although previous cross-sectional studies showed higher physical function impairment in lung cancer patients vs other cancers, 30 recent prospective studies also suggested findings similar to our study such that function decline or trajectory are not associated with the type of cancer diagnosis but may be associated with type of cancer treatments and new cancer diagnosis. 31,32 Future studies should investigate whether the association between symptoms burden and physical function is moderated by cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous cross-sectional studies showed higher physical function impairment in lung cancer patients vs other cancers, 30 recent prospective studies also suggested findings similar to our study such that function decline or trajectory are not associated with the type of cancer diagnosis but may be associated with type of cancer treatments and new cancer diagnosis. 31,32 Future studies should investigate whether the association between symptoms burden and physical function is moderated by cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults with cancer are at increased risk for treatment toxicity and functional impairment, [1][2][3][4] resulting in increased healthcare use and mortality. [5][6][7][8][9][10] Maintaining functional status (FS) during cancer treatment is critically important to patients. More than 70% of older patients with cancer report that they would not choose a treatment that results in functional impairment, even if it improves survival.…”
Section: Introductionmentioning
confidence: 99%
“…For this analysis, we selected two of the most common symptomatic AEs in CALGB 9730, fatigue and neuropathy, based on their prevalence in the trial [10], clinical relevance, and impact on QOL in older adults [15][16][17][18]. Fatigue is one of the most common and distressing symptoms among older patients with NSCLC and is associated with functional decline with chemotherapy [17,19]. Neuropathy can interfere with daily activities and is associated with increased fall risk and lower QOL [16,18,20,21].…”
Section: Discussionmentioning
confidence: 99%